Optimized Control for MMCs with Reduced Power Loss and Extended Lifetime - Jifeng Zhao; Jia Pei; Yun Sun; Rujin Wang; Jun Hang; Shichuan Ding (International Transactions on Electrical Energy Systems)
Modular multilevel converters (MMCs) are widely applied to medium and high voltage occasions. The total power consumption of the submodule (SM) and the maximum power consumption of power devices in the SM are related to the operating costs and lifetime of the MMC. Existing literature only considers total power loss optimization or maximal power consumption optimization in MMC’s SM. In this article, a reduced loss and extended lifetime power loss optimum control (RLEL-PLOC) is introduced to inject the first-best second harmonic circulation into the MMC’s arm current. Compared with the conventional power loss optimization control, the proposed control could decrease the maximal power consumption of the semiconductor devices without increasing the total loss of the SM. According to study results of the MMC, compared with the circulating current suppression control (CCSC) method, the total power consumption of the SM could be reduced by 4.2% and the maximal power dissipation in the SM could be reduced by 5.4% with RLEL-PLOC. PSCAD simulation and MMC prototype experiment are also carried out, and the research results verified the availability of the put forward RLEL-PLOC for MMCs.